Neutrophils: Innate Effectors of TB Resistance? - Kroon, Elouise E.; Coussens, Anna K.; Kinnear, Craig; Orlova, Marianna; Möller, Marlo; Seeger, Allison; Wilkinson, Robert J.; Hoal, Eileen G.; Schurr, Erwin (Frontiers in Immunology, 2018)
Certain individuals are able to resist Mycobacterium tuberculosis infection despite persistent and intense exposure. These persons do not exhibit adaptive immune priming as measured by tuberculin skin test (TST) and interferon-γ (IFN-γ) release assay (IGRA) responses, nor do they develop active tuberculosis (TB). Genetic investigation of individuals who are able to resist M. tuberculosis infection shows there are likely a combination of genetic variants that contribute to the phenotype. The contribution of the innate immune system and the exact cells involved in this phenotype remain incompletely elucidated. Neutrophils are prominent candidates for possible involvement as primers for microbial clearance. Significant variability is observed in neutrophil gene expression and DNA methylation. Furthermore, inter-individual variability is seen between the mycobactericidal capacities of donor neutrophils. Clearance of M. tuberculosis infection is favored by the mycobactericidal activity of neutrophils, apoptosis, effective clearance of cells by macrophages, and resolution of inflammation. In this review we will discuss the different mechanisms neutrophils utilize to clear M. tuberculosis infection. We discuss the duality between neutrophils' ability to clear infection and how increasing numbers of neutrophils contribute to active TB severity and mortality. Further investigation into the potential role of neutrophils in innate immune-mediated M. tuberculosis infection resistance is warranted since it may reveal clinically important activities for prevention as well as vaccine and treatment development.